2014
DOI: 10.1177/1477153514528934
|View full text |Cite
|
Sign up to set email alerts
|

A study of atmosphere perceptions in a living room

Abstract: An experiment has been carried out to investigate the effect of lighting on the perception of atmosphere in a living room, using three types of light sources: halogen, fluorescent and LED lamps. In a psychophysical experiment, 29 native Chinese observers assessed eight lighting conditions having different luminances and correlated colour temperatures. For each condition, 71 scales were employed using the categorical judgment method. Factor analysis identified two underlying dimensions: liveliness and cosiness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 9 publications
4
30
1
Order By: Relevance
“…This implies that an increase in CCT would make paintings to appear brighter and cooler. These two findings confirm earlier findings 14,20 .…”
Section: Effect Of Cct On Perceptionssupporting
confidence: 95%
“…This implies that an increase in CCT would make paintings to appear brighter and cooler. These two findings confirm earlier findings 14,20 .…”
Section: Effect Of Cct On Perceptionssupporting
confidence: 95%
“…This agrees with our earlier findings. 18 The trend in Figure 6(b) is obviously stronger than Figure 6(a), i.e. the range of the score in Figure 6(b) is larger than that in Figure 6(a).…”
Section: Inter-observer Variationmentioning
confidence: 87%
“…Atmosphere is not an affective state in itself, but an affective evaluation of the environment [ 11 ]. Past studies have shown that atmosphere can be characterized along four dimensions, namely coziness, liveliness, detachment and tenseness [ 11 ], of which liveliness and coziness are the most important ones [ 11 , 43 ]. Alternatively, atmosphere may be evaluated in terms of valence and arousal [ 44 , 45 ].…”
Section: Related Workmentioning
confidence: 99%
“…The relation between both characterizations of atmosphere is that coziness was found to be positively correlated with positive valence and negatively correlated with arousal, while liveliness was found to be positively correlated with both valence and arousal [ 12 ]. Extensive knowledge has been built up about the influence of lighting characteristics on atmosphere perception [ 12 , 13 , 43 , 46 ]. The combination of general white lighting with colored accent lighting is known to be able to generate cozy, activating and exciting atmospheres in a room for younger people [ 12 , 47 ].…”
Section: Related Workmentioning
confidence: 99%